Semântica filosófica em Wittgenstein: Uma noção de significado nas investigações. - Freitas, Edivaldo Simão de (2018)
The following paper presents a study which aims to describe the stages Wittgenstein went through in order to present his new philosophical semantic paradigm in Philosophical Investigations (PI). Such stages are centered on the following axes: (i) the critique of the augustinian picture of language in order to base a new linguistic image as well as a new semantic image; (ii) exposition of ostensive teaching as a pedagogical practice which bases the learning of words on people's use of them; (iii) terminological apprehension of the word Bedeutung, classifying it as a fundamental term for wittgensteinian semantics; (iv) exposition of conceptual categories for the construction of a new way of thinking about meaning, these categories are as follow: language games, family resemblaces, forms of life and following rules.